Determination of Customer Loyalty Through Customer Satisfaction in Using Mobile Banking - Ulya, Zikriatul; alfian; Zuhra, Nur rahmi; Setiawan, Muarif (Jurnal Manajemen dan Keuangan, 2025)
This study aims to analyze the determinants that influence customer loyalty through customer satisfaction in using mobile banking . The method used in this study is a quantitative descriptive approach using path analysis to test the direct relationship between variables and indirect relationships between variables using structural equation modeling - partial least square (sem-pls). Data collection used is a questionnaire distributed via google form. The number of samples is 90 Aceh Tamiang customers. Determination of the sample uses a nonprobability sampling technique where sampling does not provide equal opportunities for each member of the population selected as a sample and uses SmartPLS 4.0 software. The results of the study showed that the customer experience variable on customer satisfaction has a positive and significant effect, the service quality variable on customer satisfaction has a negative and insignificant effect, the service feature variable on customer satisfaction has a positive and significant effect, the customer experience variable on customer loyalty has a negative and insignificant effect, the service quality variable on customer loyalty has a negative and insignificant effect, the service feature variable on customer loyalty has a positive and significant effect, the customer satisfaction variable on customer loyalty has a positive and significant effect, customer satisfaction can mediate customer experience on customer loyalty, customer satisfaction cannot mediate service quality on customer loyalty, customer satisfaction can mediate service features on customer loyalty.